2020
DOI: 10.1186/s41100-020-00280-1
|View full text |Cite
|
Sign up to set email alerts
|

Range of plasma brain natriuretic peptide (BNP) levels in hemodialysis patients at a high risk of 1-year mortality and their relationship with the nutritional status: a retrospective cohort study in one institute

Abstract: Background: Brain natriuretic peptide (BNP) levels are used as a marker of heart failure, which is the leading cause of morbidity and mortality in dialysis patients. BNP levels increase as renal function declines. The range of BNP levels associated with satisfactory longevity in dialysis patients currently remains unknown. Methods: In total, 660 patients receiving maintenance hemodialysis were enrolled. BNP levels were measured at the end of the year and in a follow-up to assess 1-year mortality between 2008 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Chertow et al reported that TTR levels correlated with age, sex, diabetes, body weight, blood urea nitrogen, creatinine, albumin, phosphorus, and bicarbonate relative to TTR >40 mg/dl, and the adjusted relative risks were 2.41, 1.85, 1.49, and 1.23, for TTR levels <15, 15 to <20, 20 to <25, and 25–30 mg/dl, respectively [4]. We reported in our previous report that BNP levels showed the strongest correlation with TTR levels, and, after adjustment for TTR levels, the risk associated with high BNP levels was no longer significant [15]. Based on the above, we concluded that TTR is the strongest independent predictive factor for 1‐year mortality in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chertow et al reported that TTR levels correlated with age, sex, diabetes, body weight, blood urea nitrogen, creatinine, albumin, phosphorus, and bicarbonate relative to TTR >40 mg/dl, and the adjusted relative risks were 2.41, 1.85, 1.49, and 1.23, for TTR levels <15, 15 to <20, 20 to <25, and 25–30 mg/dl, respectively [4]. We reported in our previous report that BNP levels showed the strongest correlation with TTR levels, and, after adjustment for TTR levels, the risk associated with high BNP levels was no longer significant [15]. Based on the above, we concluded that TTR is the strongest independent predictive factor for 1‐year mortality in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%